Comparison of the take-off ground reaction force patterns of the pole vault and the long jump - Plessa, E. I.; Rousanoglou, E. N.; Boudolos, K. D. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The take-off is probably the most important phase of the pole vault. The kinematics of pole vault take-off is often described in comparison to the long jump take-off. If a kinetic similarity were also evidenced, the extra loading of carrying the pole could be avoided by using the long jump style take-off drills in pole vault take-off training. However, to our knowledge, a direct comparison of the take-off ground reaction force (GRF) pattern of the two types of jump has not been reported in the scientific or coaching literature. The purpose of this study was to compare the take-off GRF patterns of the support leg in the pole vault and the long jump. METHODS: Twelve elite women jumpers undertook pole vault and long jump trials. The take-off GRF patterns were recorded by a force plate (Kistler-9286AA). Temporal and force parameters were determined for all three GRF components. Trials were videotaped to determine the take-off kinematics. Paired sample t-tests (SPSS 13.0) were applied (P=0.05) for comparison between jumps. RESULTS: No significant differences were found in kinematics (P>0.05). Overall, the GRF patterns were similar, although there were particular significant (P=0.05) differences in contact times, impulses and force peaks. CONCLUSION: This study provides scientific support for potential use of the long jump take-off drills during technical preparation for the pole vault take-off.